All‐In‐One Integrated Multifunctional Broadband Metasurface for Analogue Signal Processing, Polarization Conversion, Beam Manipulation, and Near‐Field Sensing. Issue 20 (29th July 2022) - Liu, Baiyang; Du, Jiachen; Jiang, Xiaonan; Li, Yin; Wong, Sai‐Wai; Cheng, Qiang; Cui, Tie Jun; Zhang, Qingfeng
Abstract: Programmable metasurface, or reconfigurable intelligent surface is one of the most promising strategies to enhance communication and sensing capacities via arrays of reconfigurable meta‐atoms. The functionalities of conventional programmable metasurfaces are usually limited, and active meta‐atoms are connected with steering‐logic board through cables, which makes the whole system inconvenient for installation and stable use. Here an all‐in‐one integrated multifunctional metasurface for various application purpose is proposed. The integration of metasurface and steering‐logic board produces an all‐in‐one system, which makes it compact, low profile, and stable. The novel meta‐atom structure provides all‐in‐one functionalities, including 1) dispersion‐reconfigurable spatial phaser for analogue signal processing, 2) polarization conversion, 3) beam steering and orbital angular momentum generation for high‐speed communication and, 4) near‐field scanning for sensing. The proposed metasurface also has a broadband property, which is operating from 9.5 to 10.5 GHz with 10% relative bandwidth. Such a design integrates functionalities of signal processing, communication, and sensing in a single programmable metasurface, which makes it especially useful for integrated sensing and communication toward next‐generation wireless networks. Abstract : An all‐in‐one integrated multifunctional metasurface is proposed here. The integration of metasurface and steering‐logic board produces an all‐in‐one system, which makes it compact, low profile, and stable. The novel meta‐atom structure provides all‐in‐one functionalities, including dispersion‐reconfigurable spatial phaser for analogue signal processing, polarization conversion, beam steering, and orbital angular momentum generation for high‐speed communication, and near‐field scanning for sensing.